A comparative microbiological study of the essential oils from the genus Rosa L. - Odyntsova, V. M.; Polishchuk, N. М.; Denysenko, O. M.; Mozul, V. I.; Holovkin, V. V.; Zhyvora, N. V.; Rudko, Ye. V.; Одинцова, Віра Миколаївна; Поліщук, Наталія Миколаївна; Денисенко, Ольга Миколаївна; Мозуль, Валентина Іванівна; Головкін, Володимир В'ячеславович; et al. (My University, 2024)
Aim. To conduct a comparative microbiological study of essential oils from Rosa damascena of the “Veselka” variety grown via clonal micropropagation in in vitro culture and in the natural environment of Zaporizhzhia. Materials and methods. The study objects were essential oils obtained by water distillation from rose petals cultivated using the method of clonal micropropagation in in vitro culture (at the premises of the Educational and Scientific Medical Laboratory Center with a vivarium) and the natural environment of Zaporizhzhia. The study of the antimicrobial activity was conducted in the microbiological laboratory of the Department of Microbiology, Virology, and Immunology at Zaporizhzhia State Medical and Pharmaceutical University. Results and discussion. The essential oils from Rosa damascena grown via clonal micropropagation in in vitro culture and under natural conditions in Zaporizhzhia effectively inhibited the growth of E. coli (21.3 mm and 12.0 mm, respectively) and S. aureus (11.3 mm and 10.2 mm, respectively). The results of the study on C. albicans indicate a high antifungal activity in both essential oils; the mean inhibition zone diameter in the experiments using the oil from Rosa damascena cultivated in in vitro culture is less: 33.3 mm compared to 40 mm in the experiments with the oil from roses grown in the natural environment of Zaporizhzhia. Conclusions. The method of clonal micropropagation of Rosa damascena of the “Veselka” variety is effective for obtaining a large amount of planting material in a short time with the subsequent reintroduction into the natural environment to expand the raw material base of valuable medicinal plants with a high content of essential oils. The results of the study of the antimicrobial activity of the essential oil of Rosa damascena of the “Veselka” variety cultivated through clonal micropropagation in in vitro culture have exhibited a high antimicrobial activity and moderate antifungal activity compared to the essential oil from Rosa damascena grown in the natural environment of Zaporizhzhia. Therefore, Rosa damascena Mill. of the “Veselka” variety cultivated under in vitro conditions is a promising source of essential oil with a high antibacterial effect in order to create new herbal formulations. Метою роботи було порівняльне мікробіологічне дослідження ефірних олій троянди дамаської сорту Веселка, вирощеної методом клонального мікророзмноження в культурі in vitro та в природному середовищі в умовах м. Запоріжжя. Матеріали та методи. Об’єктами дослідження були ефірні олії, отримані методом гідродистиляціїї з пелюсток троянд, вирощених методом клонального мікророзмноження в культурі in vitrо (на базі Навчально-наукового медико-лабораторного центру з віварієм) та в природному середовищі в умовах м. Запоріжжя. Дослідження протимікробної активності проведено на базі мікробіологічної лабораторії кафедри мікробіології, вірусології та імунології Запорізького державного медико-фармацевтичного університету. Результати та їх обговорення. Ефірні олії троянди дамаської, вирощеної методом клонального мікророзмноження в культурі in vitrо та в природному середовищі в умовах м. Запоріжжя, досить ефективно пригнічували зрос- тання E. coli (відповідно 19,7 та 12,0 мм) та S. aureus (відповідно 11,3 та 10,2 мм). Результати дослідження з C. albicans свідчать про високу протигрибкову активність обох ефірних олій, середнє значення діаметра зони затримки зростання в експериментах з олією троянди дамаської, вирощеної в культурі in vitrо, є меншим: 33,3 мм проти 40 мм в експериментах з ефірною олією троянди, вирощеної в природному середовищі в умовах м. Запоріжжя. Висновок. Метод клонального мікророзмноження троянди дамаської сорту Веселка ефективний для одержання великої кількості посадкового матеріалу в короткі строки з подальшою реінтродукцією в природне середовище для розширення сировинної бази цінних лікарських рослин з високим вмістом ефірних олій. Результати дослідження протимікробної активності ефірної олії троянди сорту Веселка, вирощеної методом клонального мікророзмноження в культурі in vitrо, проти ефірної олії троянди дамаської, вирощеної в природному середовищі в умовах м. Запоріжжя, засвідчили високу антибактеріальну та помірну протигрибкову активність. Rosa damascena Mill. сорту Веселка, вирощена в умовах in vitro, є перспективним джерелом отримання ефірної олії з високою антибактеріальною властивістю з метою створення нових фітопрепаратів.
Порівняльне мікробіологічне дослідження ефірної олії представників роду Rosa L.
Keywords: Rosa damascena Mill. “Veselka” variety; clonal micropropagation in in vitro culture; essential oil; antimicrobial activity; Rosa damascene Mill. сорту Веселка; клональне мікророзмноження в культурі in vitrо; ефірна олія; протимікробна активність